Acceptance and purchase intention of irradiated foods in Brazil: Effect of positive information - Martins, Cecilia G. (2012)
Food irradiation remains underutilized in Brazil, despite the approval and regulation of the official health authority since 1973. However, consumers risk perception, mostly due to lack of information about the technology, seem to be the main barrier to the adoption of food irradiation by the Brazilian industries, like in other countries. The aim of this study was to investigate the effect of information on the acceptance and purchase intention of minimally processed and irradiated organic watercress (Nasturtium officinale). Consumers (N=236) participating in the sensory acceptance test were divided into four experimental groups according to an experimental design which combined presence or absence of information about the food irradiation process – main characteristics, benefits to food safety and preservation, cost-benefit and environmental issues - and identification or not of the irradiated product in a sensory acceptance test. Results did not show significant effect (p>0.05) of information either on acceptability or in purchase intention of the irradiated product compared to the non irradiated counterpart, although an exploratory statistical analysis revealed underlying patterns suggesting that consumers segmentation must exist as well as favorable and unfavorable attitude to food irradiation.